2011
DOI: 10.1007/s10194-011-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with aura in the locker room: three case reports

Abstract: It is well known that physical activity can aggravate the intensity of the headache, but the pathophysiological relationship between exertion and aura is still unknown. Anecdotal reports describe episodes of migraine preceded by head trauma and visual symptoms, migraine prodrome symptoms after unusually strenuous running with no subsequent head pain or recurrent attacks of hemiplegic migraine induced only by exertion. We describe the cases of three young men with recurrent episodes of migraine with aura occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Our demonstration that the sensory pathway by which a noxious stimulus applied to the foot can bypass an interrupted spinal cord explains Nathan's original observation (Villanueva et al, 2006) as well as more recent work (Wrigley et al, 2018). While the entity referred to as jogger's migraine (Corbelli et al, 2012) might be explained by this pathway (although not the preceding aura), its end-point—facial vasodilation mediated by beta-adrenergic receptors—supports recent work suggesting a far greater contribution of neurovascular dysfunction to migraine pathophysiology via antidromic vasodilation (Geppetti et al, 2012) and the mechanism by which beta-blockers prevent attacks (Jacobs and Dussor, 2016). This pathway also identifies one potential mechanism for some of the positive effects of acupuncture [often applied to the ipsilateral foot (Silberstein, 2009)] in treating episodic migraine, and may have additional implications for the mechanism by which acupuncture exerts its effect (Linde et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our demonstration that the sensory pathway by which a noxious stimulus applied to the foot can bypass an interrupted spinal cord explains Nathan's original observation (Villanueva et al, 2006) as well as more recent work (Wrigley et al, 2018). While the entity referred to as jogger's migraine (Corbelli et al, 2012) might be explained by this pathway (although not the preceding aura), its end-point—facial vasodilation mediated by beta-adrenergic receptors—supports recent work suggesting a far greater contribution of neurovascular dysfunction to migraine pathophysiology via antidromic vasodilation (Geppetti et al, 2012) and the mechanism by which beta-blockers prevent attacks (Jacobs and Dussor, 2016). This pathway also identifies one potential mechanism for some of the positive effects of acupuncture [often applied to the ipsilateral foot (Silberstein, 2009)] in treating episodic migraine, and may have additional implications for the mechanism by which acupuncture exerts its effect (Linde et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…(D,E) Application of capsaicin to lower thigh of immersed limb did not result in an increase in facial blood flow in healthy controls undergoing warm water immersion only without nociceptive challenge. The small reduction in ipsilateral facial blood flow only identified immediately after capsaicin application may reflect a direct vasoconstrictive effect (Keeble and Brain, 2006; Corbelli et al, 2012). #Change from baseline statistically significant ( p < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…The authors also investigated strenuous physical exercise-induced migraine and found that attacks were triggered in four patients out of 12, whereas an additional three out of seven patients developed headache after the combined exposure to light stimulation and exercise. The possible triggering role of strenuous exercise in migraine with aura is supported by a few other case reports [47]. This could be explained by considering that exerciseinduced dehydration, and consequently hyperthermia, reduces cerebral oxygenation [48], possibly promoting the genesis of a wave of cortical spreading depression.…”
Section: Provocation and Causalitymentioning
confidence: 83%
“…Two reported cases of aura were triggered following air microbubble injection during transcranial Doppler ultrasound examination (44,45). Three studies reported aura induced by physical activity (4649) and one following orgasm (47). Two studies reported aura after the consumption of two different food sources (50,51).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the reviewed studies used physical activity for the provocation of aura, with a total trigger rate of 18% (8,20). In addition, three case reports of aura triggered by physical activity were identified (46,48,49). These studies suggested that different types of strenuous physical activity may induce aura.…”
Section: Aura Induced By Physical Activitymentioning
confidence: 99%